Correlation between Running Surface Types and Risk of Iliotibial Syndrome - Rizki Setiawan; Farid Rahman (Universitas Pendidikan Indonesia, 2023)
Running is a mostly performed sport by people, but it is important to pay attention to the running surface because it can be a factor of injuries experienced by runners. Running on a road runner track is preferred because it can reduce injuries by 32.4%. A study from the Vancouver Running Clinic, the frequency of experiencing Iliotibial Band Syndrome (ITBS) was 6.8% for men and 9.8% for women. This research was aimed to determine the relationship between the type of running surface and Iliotibial Band Syndrome (ITBS) injuries. This research is a correlational study using cross sectional approach. In this research, the non-probability sampling and incidental sampling techniques were used. This research involved 80 runners in the Special Region of Yogyakarta and Magelang City as subjects. The data collection instruments for this research included the Ober test for ITBS and a questionnaire for respondent history. Analysis of data regarding the relationship between the type of running surface and the incidence of Iliotibial Band Syndrome found no relationship. It shows that the type of running surface does not affect the incidence of Iliotibial Band Syndrome (ITBS) in runners. It is expected that this research can become a baseline or foundation for developing prevention of Iliotibial Band Syndrome.